Forming a collective Brand: Women’s community small medium enterprises and intellectual property rights - Widiastuti, Tuti; Asiah, Nurul; David, Wahyudi (ASEAN Journal of Community Engagement, 2020)
Women, as part of a community, have a limited role in developing themselves and getting various opportunities in the professional domain. Some women move to a community to conduct productive activities, such as the Kota Pelangi Community in the Pancoran subdistrict of South Jakarta. They consist of homemakers who are still productive and have started various small, processed food businesses. However, their efforts are constrained by the quality of processed food products and they have not been able to compete with the market. Branding or updating a brand can be a long process, but it requires considerable input and creativity. Brands that go through the collective branding process too quickly risk being unprofessional and not being taken seriously. This community service program assists with licensing and branding the community’s product. The first aspect is improving product quality through innovation and the use of technology. Next is branding development and increased sales packaging through e-commerce marketing assistance, which includes displaying products in various bazaars and exhibitions. It is also necessary to conduct business financial management and bookkeeping training. Last is the provision of aid for licensing and capital management. The program was conducted to encourage and increase entrepreneurial women's productivity in the Pancoran subdistrict to develop skills, including soft skills, to be economically and socially independent.